Tinjauan Etika Birokrasi terhadap Penegakan Sanksi Administratif bagi Toko Berjejaring oleh Satuan Polisi Pamong Praja di Kabupaten Bantul - Adik Miftakhur Rohmah (Badan Perencanaan Pembangunan Daerah Kabupaten Bantul, 2026)
This study aims to analyze the enforcement of administrative sanctions against chain stores by the Civil Service Police Unit (Satpol PP) in Bantul Regency, reviewed from the perspective of bureaucratic ethics, particularly the professional ethics of Civil Servant Investigators (PPNS). The problem arises from a gap between the provisions of Bantul Regency Regional Regulation Number 21 of 2018 on the Organization of Traditional Markets, Self-Service Stores, and Shopping Centers, and its enforcement practices in Bantul Regency. The Bantul Regency Satpol PP has failed to enforce administrative sanctions against chain stores that violate distance requirements, citing changes in licensing nomenclature following the enactment of Government Regulation Number 28 of 2025 on the Implementation of Risk-Based Business Licensing. This study employs a normative legal research method, using primary and secondary legal materials analyzed through description, systematization, analysis, and evaluation of positive law. The findings indicate that changes in licensing nomenclature cannot constitute a valid legal basis for disregarding the enforcement of administrative sanctions, and that the prevailing practice is contrary to the professional ethics principles of PPNS.